2021
DOI: 10.2169/internalmedicine.6105-20
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Post-intubation Laryngotracheal Stenosis Occurring after Severe COVID-19

Abstract: We experienced two cases of post-intubation laryngotracheal stenosis (PILS) occurring in patients after acute coronavirus disease (COVID)-19 in a relatively narrow time period. The patients required mechanical ventilation for 9 days in one and 28 days in the other. In both cases, the patients were discharged but later developed symptoms of cough and dyspnea, which were later diagnosed as PILS. Persistent cough and dyspnea are common symptoms in both PILS and the recovery phase of severe COVID-19. For this reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
21
0
2
Order By: Relevance
“…PILS becomes symptomatic (1–2% of cases) when the stenosis includes >60% of the tracheal lumen. Previous reports showed that the time of onset of PILS varied from 28 days to 6 months after extubation [ 3 ]. The most common cause of PILS is iatrogenic [ 7 ], specifically in prolonged intubations, endotracheal tube cuff hyperinflation, and the usage of large tubes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PILS becomes symptomatic (1–2% of cases) when the stenosis includes >60% of the tracheal lumen. Previous reports showed that the time of onset of PILS varied from 28 days to 6 months after extubation [ 3 ]. The most common cause of PILS is iatrogenic [ 7 ], specifically in prolonged intubations, endotracheal tube cuff hyperinflation, and the usage of large tubes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the global trend for COVID-19 patients admitted to ICU is to postpone tracheostomy until the patient no longer needs mechanical ventilation and is cleared of the virus; this delay is mainly due to the high risk of cross-infection of healthcare professionals [ 6 ]. Early reports state that COVID-19 patients remained intubated from one to two weeks or longer [ 3 ]. In our case, one patient underwent 3 weeks and the other 8 weeks of mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations